Effect of Leifsonia sp. on retardation of uranium in natural soil and its potential mechanisms. (June 2020) - Tan, Wen-fa; Li, Yuan; Guo, Feng; Wang, Ya-chao; Ding, Lei; Mumford, Kathryn; Lv, Jun-wen; Deng, Qin-wen; Fang, Qi; Zhang, Xiao-wen
Abstract: Uranium mining and milling activities for many years resulted in release of uranium into the adjoining soil in varying degrees. Bioremediation approaches (i.e., immobilization via the action of bacteria) resulting in uranium bearing solid is supposed as an economic and clean in-situ approach for the treatment of uranium contaminated sites. This study purposes to determine the immobilization efficiency of uranium in soil by Leifsonia sp. The results demonstrated that cells have a good proliferation ability under the stress of uranium and play a role in retaining uranium in soil. Residual uranium in active Leifsonia -medium group (66%) was higher than that in the controls, which was 31% in the deionised water control, 46% in the Leifsonia group, and 47% in the medium group, respectively. This indicated that Leifsonia sp. facilitates the immobilization efficiency of uranium in soil by converting part of the reducible and oxidizable fraction of uranium into the residual fraction. X-ray photoelectron fitting results showed that tetravalent states uranium existed in the soil samples, which indicated that the hexavalent uranium was converted into tetravalent by cells. This is the first report of effect of Leifsonia sp. on uranium immobilization in soil. The findings implied that Leifsonia sp. could, to some extent, prevent the migration and diffusion of uranium in soil by changing the chemical states into less toxicity and less risky forms. Highlights: Column tests were carried out to determine the effect of Leifsonia sp. on U(VI). Part of the reducible and oxidizable fraction of U(VI) were converted into the residual fraction. Leifsonia sp. can to a certain extent immobilize U(VI) in soil.